1999
DOI: 10.1289/ehp.99107s4639
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of potential endocrine-related health effects at low-dose levels of exposure to PCBs.

Abstract: This article addresses issues related to the characterization of endocrine-related health effects resulting from low-level exposures to polychlorinated biphenyls (PCBs). It is not intended to be a comprehensive review of the literature but reflects workshop discussions. "The Characterizing the Effects of Endocrine Disruptors on Human Health at Environmental Exposure Levels," workshop provided a forum to discuss the methods and data needed to improve risk assessments of endocrine disruptors. This article contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
158
1
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 305 publications
(165 citation statements)
references
References 118 publications
(91 reference statements)
1
158
1
2
Order By: Relevance
“…51,52 Reports have also shown that marine fish contaminated with environmental toxins, such as polychlorinated biphenyls or methylmercury compounds, can disrupt androgen and estrogen balance and could be linked to high-grade prostate cancer. [53][54] Furthermore, the presence of long chain n-3 PUFA (DHA and EPA) in the prostate cell's betaoxidative metabolic process leads to the formation of lipid hydroperoxides in the microenvironment of the cell; this can generate reactive species. [55][56] With chronic exposure to these reactive molecules, the prostate cell can become dysplastic and develop into an aggressive cell.…”
Section: Discussionmentioning
confidence: 99%
“…51,52 Reports have also shown that marine fish contaminated with environmental toxins, such as polychlorinated biphenyls or methylmercury compounds, can disrupt androgen and estrogen balance and could be linked to high-grade prostate cancer. [53][54] Furthermore, the presence of long chain n-3 PUFA (DHA and EPA) in the prostate cell's betaoxidative metabolic process leads to the formation of lipid hydroperoxides in the microenvironment of the cell; this can generate reactive species. [55][56] With chronic exposure to these reactive molecules, the prostate cell can become dysplastic and develop into an aggressive cell.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies conducted in Shanghai, including this one, have consistently found that fish intake is related to an increased risk of several cancers, including cancers of breast, endometrium, and colorectum (Shu et al, 1993;Guo et al, 1994;Dai et al, 2002;Chiu et al, 2003), suggesting that water pollution may be involved in the aetiology of these cancers. Organochlorines have been shown to have estrogenic activity (Olea et al, 1998;Brouwer et al, 1999) and may increase the risk of hormone-related cancers such as prostate and breast cancer (Terry et al, 2003). However, results from two studies that have directly evaluated the association between organochlorines and endometrial cancer found either no significant association (Weiderpass et al, 2000) or a negative association (Sturgeon et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…PCBs may have variable degrees of impact depending on which congeners or congener mixtures are involved, the organism's age at exposure, the sex of the individual, the degree of exposure and the availability of compensatory diet or social buffering to counteract those effects. An accurate evaluation of ecologically relevant xenobiotic exposure (Battershill, 1994;Brouwer et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…PCBs may have variable degrees of impact depending on which congeners or congener mixtures are involved, the organism's age at exposure, the sex of the individual, the degree of exposure and the availability of compensatory diet or social buffering to counteract those effects. An accurate evaluation of ecologically relevant xenobiotic exposure (Battershill, 1994;Brouwer et al, 1999).The neuroendocrine system serves as an interface between the central nervous system and peripheral endocrine organs, and thus represents a prime target for endocrine disruption by PCBs (Patisaul et al, 2006). PCBs and their metabolites can act at multiple nodes of the neuroendocrine axis: they may serve as hormone mimics (Connor et al, 1997), alter circulating hormone levels (Desaulniers et al, 1999), change patterns of estrous cyclicity (Meerts et al, 2004;Buitenhuis et al, 2004), disrupt hormone metabolism Kester et al, 2000;Yamane et al, 1975), influence endocrine-related and hypothalamic gene expression (Aluru et al, 2004;Bansal et al, 2005;Colciago et al, 2005;Flouriot et al, 1995;Gore et al, 2002;Pravettoni et al, 2005;Salama et al, 2003), interfere with hormone binding proteins (Brouwer and van den Berg, 1986;Chauhan et al, 2000), alter neuronal signaling to endocrine regions of the brain (Khan and Thomas, 2001;Morse et al, 1996;Seegal et al, 1985;Seegal et al, 1990) or indirectly affect steroid receptor availability via molecular crosstalk (Brunnberg et al, 2003;Pearce et al, 2004).…”
mentioning
confidence: 99%
See 1 more Smart Citation